THE EFFECT OF ABDOMINAL STRETCHING EXERCISE ON DYSMENORRHEA IN ADOLESCENT GIRLS - Murtiningsih Murtiningsih; Lilis Solihah; Sri Yuniarti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Based on my survey in February 2018 at the three SMA Negeri Cimahi, 956 adolescent girls (67.2%) from 1.422 of female students had experienced dysmenorrhea. Dysmenorrhea is disturbed young women’s study activities at school. The preliminary study found that 10 teenagers had dysmenorrhea, 4 of them said they could not follow the sporting activities. This research aimed to determine the effect of abdominal stretching exercise in reducing the pain due to dysmenorrhea in the adolescent girls. The method used a quasi-experiment design with one group pretest-posttest. The population in this study was 174 peoples and obtained 19 samples with random sampling technique. Pain score measured by the Verbal Descriptor Scale before and after given the abdominal stretching exercises for 15 minutes, 3 times during 7 days with an interval of one day. Data analysis used univariate test and t-dependent test. The results of the study obtained the pain score before the abdominal stretching exercises were 6.16 scale (moderate pain) and after abdominal stretching exercises was 2.37 scale (mild pain) with pain scale difference 3.79. T-dependent statistical test obtained that p-value < 0,001, it refers to abdominal stretching exercises affects in decreasing pain scale of dysmenorrhea. Abdominal stretching exercises are recommended as an influential intervention of dysmenorrhea for adolescent girls. This exercises can be a new routine activity for adolescent girls since it is very beneficial for them.Keywords: Abdominal stretching, adolescent girls, dysmenorrhea, exercises.